THE RELATIONSHIP BETWEEN EMOTION REGULATION AND FORGIVENESS IN CLASS XI STUDENTS OF SMA NEGERI 12 BUNGO - Dhinulleily, Syafrima; Solina, Wira; Dianto, Mori (LP2M IAI Al-Khairat Pamekasan, 2025)
This research is motivated by the fact that there are students who avoid friends who have problems and prefer not to solve their problems or forgive friends who have problems. The purpose of this research is to describe 1) the regulation of students' emotions, 2) the attitude of forgiveness of students, and 3) the relationship between emotional regulation and forgiveness in students. This study was conducted using a correlational descriptive quantitative method, a population of 206, and a sampling technique using stratified random sampling with a sample number of 136. The instrument used in this study is a questionnaire. The data analysis in this study is percentage and correlational. The results of this study revealed that: 1) Emotional regulation is in the good category, 2) Forgiveness is in the poor category, and 3) There is a relationship between emotional regulation and forgiveness with a moderate correlation. This research is recommended by students to be able to monitor emotions, evaluate the emotions experienced, and modify the emotions experienced into a good attitude, to students so that they can better harmonize their emotional regulation skills so that they can increase the attitude of forgiveness or forgiveness in students, and to BK teachers so that they can provide services on ways or tips in regulating students' emotions.